Features of the recovery of the pumping function of the heart of athletes with disabilities after exercise - L. I. Vakhitov; T. L. Zefirov; I. Kh. Vakhitov (Спортивная медицина: наука и практика, 2020)
Objective: to study the reaction of heart rate and stroke volume of blood of athletes with disabilities to the implementation of standardized muscle load and the features of their recovery after completion of the load. Materials and methods: athletes are conditionally divided into two groups. The first group consists of wheelchair basketball players with amputated lower extremities. The second group consists of wheelchair basketball players with atrophy of the lower extremities. A comparative analysis of heart rate and stroke volume was carried out at rest, during muscle load and after its completion. Results: in athletes with disabilities with defects of the lower extremities, when performing a muscular load, heart rate increases by about two times compared with the initial parameters. Subsequently, heart rate values are significantly reduced. However, the rate of heart rate recovery within seven minutes of rest is not uniform. So, the most significant decrease in heart rate was observed in the second and third minutes of rest, where heart rate decreased by 17.9 and 20.1 beats/min, respectively (P<0.05). In the following minutes of rest, the heart rate recovery was significantly lower. The decrease in heart rate to the level of the initial values occurred at the seventh minute of rest. Thus, within seven minutes of rest after the completion of a 3-minute muscle load, heart rate indicators for basketball players with amputated lower limbs heart rate will return to their original values. It should be noted that basketball players with amputated lower extremities have a significantly higher heart rate at rest, according to our data, than basketball players with lower limb atrophy. It is important to emphasize that athletes with amputated lower extremities, when performing a muscle load in the form of shuttle acceleration along the perimeter of the site, responded by increasing heart rate to 155.4 beats/min, while athletes with atrophy of the lower extremities responded to the same load by increasing heart rate to 171.5 beats/min. The difference was 16.1 beats/min (P<0.05). Moreover, while basketball players with amputated lower extremities restored their heart rate to about the level of the initial values at the seventh minute of rest, in athletes with atrophy of the lower extremities, a reduction to the initial level was registered only at the 8th minute of the recovery process. Conclusions: it was found that basketball players with amputated lower extremities have higher heart rates, and the SVR values are significantly lower than basketball players with lower limb atrophy. It has been established that basketball players with amputated lower extremities respond to muscle load with greater changes in CRI than athletes with atrophied lower extremities. It was revealed that basketball players with amputated lower extremities restore heart rate and CRI to approximately the initial values after the completion of muscle load occurs much faster than basketball players with atrophy of the lower extremities.